THE ROLE OF PROCESS SKILLS APPROACH TO IMPROVE CRITICAL THINKING AND STUDENT LEARNING ACHIEVEMENT - Diah Kustinah; Turdjai Turdjai (UNIB Press, 2019)
This study aims to (1) describe the application of the process skills approach in improving students' critical thinking, (2) describe the application of the process skills approach in increasing student achievement, (3) describe the effectiveness of the application of the process skills approach in improving student learning achievement. This research was carried out using Classroom Action Research (CAR) and quasi-experimental. The data collection method in this study used an observation sheet to measure the teacher's ability to apply the Process Skills approach and students' critical thinking abilities, as well as a test to measure student learning achievement improvement. For data analysis, the analysis used mean score analysis and t-test. Based on the results of research conducted in three cycles in class XII IPA 1, this research resulted in the following conclusions: (1) The application of the process skills approach can improve students' critical thinking skills, (2) The application of the process skills approach can improve student achievement, (3) The application of process skills effectively improves student achievement in Biology subjects